Variational Analysis and Generalized Differentiation in Optimization and Control In Honor of Boris S. Mordukhovich - Burachik, Regina S.; Yao, Jen-Chih.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Variational analysis is a rapidly growing field within pure and applied mathematics, with numerous applications to optimization, control theory, economics, engineering, and other disciplines. This volume brings together state-of-the-art results in variational analysis and its applications, with an emphasis on optimization and control. The included chapters, written by international experts in the field of variational analysis and related topics, are dedicated to Boris S. Mordukhovich, a renowned mathematician, and aim to celebrate his fundamental contributions to variational analysis, generalized differentiation and their applications. This volume is intended for mathematicians studying variational analysis as well as other researchers interested in applying the principles of variational analysis to their area of study.
Systems of Vector Quasi-equilibrium Problems and Their Applications -- Properties of Derivates and Some Applications -- On Computing the Mordukhovich Subdifferential Using Directed Sets in Two Dimensions -- Future Challenges for Variational Analysis -- A Deflected Subgradient Method Using a General Augmented Lagrangian Dualitywith Implications on Penalty Methods -- On Weak Multifunction Equilibrium Problems -- Optimality Conditions for a Simple Convex Bilevel Programming Problem -- Smooth Representations of Optimal Solution Sets of Piecewise LinearParametric Multiobjective Programs -- Global Optimality Conditions for Classes of Non-convex Multi-objective Quadratic Optimization Problems -- Application of Variational Analysis and Control Theory to Nonparametric MaximumLikelihood Estimation of a Density Function -- Parametric Variational System with a Smooth-Boundary Constraint Set -- Exact Penalty in Constrained Optimization and the Mordukhovich BasicSubdifferential.
Keywords: Mathematics; Global analysis (Mathematics).; Systems theory; Mathematical optimization; Mathematics; Calculus of Variations and Optimal Control, Optimization; Systems Theory, Control; Optimization; Analysis